Compactness properties of limited operator - Afkir, F.; Elbour, A. (Methods of Functional Analysis and Topology, 2021)
The aim of this paper is to investigate the relationship between limited operators and weakly compact (resp. compact) operators. Mainly, it is proved that if every limited operator T:E→ X from a Banach lattice E into Banach space X is weakly compact (resp. compact) then the norm of E^′ is order continuous or X has the (BD) property (resp. GP property). Also, it is proved that if every weakly compact operator T:E→ X is limited then the norm of E^′ is order continuous or X has the DP^* property. Метою цієї роботи є дослідження зв’язку між обмежувальними операторами та слабо компактними (відповідно компактними) операторами. Доведено, що якщо кожен обмежувальний оператор T : E→ X з банахової ґратки E в банаховий простір X є слабо компактним (відповідно компактним), то норма в E^′ є порядково неперервною або X має (BD)-властивість (відповідно GP-властивість). Також доведено, що якщо кожний слабо компактний оператор T : E→ X обмежений, то норма в E^′ є порядково неперервною або X має DP^* -властивість.